Факторы и основания религиозной толерантности в Республике Казахстан (ҚазҰУ Хабаршысы. Дінтану сериясы, 2017)
The article is dedicated to the formation and development of the policy of religious tolerance and the factor of tolerant interaction in modern society and culture. The article deals with the causes of the increased influence of religion in modern society, shows the conditions of the formation of the factors of religious tolerance, reveals the evolution of evaluation of tolerant behavior and communication in society and religious environment, clarifies some patterns of increased influence of religious tolerance in contemporary social structures and institutions of society.